Spectrophotometric Determination of Itopride Hydrochloride in Pharmaceutical Formulations - Choragudi, Shechinah Felice; Settaluri, Vijaya Saradhi (Asian Journal of Chemistry, 2010)
A simple, sensitive and reproducible spectrophotometric method is developed for the determination of itopride hydrochloride in pharmaceutical formulations. This method is based on the formation of coloured species on binding of itopride hydrochloride with potassium ferrocyanide followed by ferric chloride to produce a blue coloured solution (λmax at 720 nm). Results of analysis were validated statistically and by recovery studies. This method is successfully employed for the determination of itopride hydrochloride in various pharmaceutical preparations.